2014
DOI: 10.1136/bmjopen-2013-003440
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural activation versus mindfulness-based guided self-help treatment administered through a smartphone application: a randomised controlled trial

Abstract: ObjectivesEvaluating and comparing the effectiveness of two smartphone-delivered treatments: one based on behavioural activation (BA) and other on mindfulness.DesignParallel randomised controlled, open, trial. Participants were allocated using an online randomisation tool, handled by an independent person who was separate from the staff conducting the study.SettingGeneral community, with recruitment nationally through mass media and advertisements.Participants40 participants diagnosed with major depressive dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
270
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(287 citation statements)
references
References 56 publications
7
270
3
7
Order By: Relevance
“…Carlbring et al (2013) and Kivi et al (2014) tested an 8-week guided Internet-delivered intervention combining components of behavioral activation and ACT. One study evaluated an 8-week guided MBCT program administered via smartphone application (Ly et al, 2014), while another examined an unguided Internetdelivered MBCT intervention (Dowd et al, 2015). An off-line computer-based CBASP treatment was tested by Braithwaite and Fincham (2007) and Cukrowicz and Joiner (2007).…”
Section: E F F I C a C Y A N D A C C E P T A B I L I T Y O F T H I R mentioning
confidence: 99%
See 1 more Smart Citation
“…Carlbring et al (2013) and Kivi et al (2014) tested an 8-week guided Internet-delivered intervention combining components of behavioral activation and ACT. One study evaluated an 8-week guided MBCT program administered via smartphone application (Ly et al, 2014), while another examined an unguided Internetdelivered MBCT intervention (Dowd et al, 2015). An off-line computer-based CBASP treatment was tested by Braithwaite and Fincham (2007) and Cukrowicz and Joiner (2007).…”
Section: E F F I C a C Y A N D A C C E P T A B I L I T Y O F T H I R mentioning
confidence: 99%
“…Participants rated the treatments as satisfactory (Trompetter et al, 2015;Lappalainen et al, 2014Lappalainen et al, , 2015, enjoyable (Glick & Orsillo, 2015), useful (Kristjánsdóttir et al, 2013), and helpful (Cukrowicz & Joiner, 2007), as measured by the Client Satisfaction Questionnaire (Attkisson & Zwick, 1982), visual analogue scales, and brief questionnaires, respectively. Four studies administered the Credibility/Expectancy Questionnaire (Borkovec & Nau, 1972;Devilly & Borkovec, 2000) and ratings indicated that participants perceived the third-wave eHealth treatments as credible (Kelly & Carter, 2015;Ljótsson et al, 2010;Ly et al, 2014). Participants rated the Internet-delivered intervention administered by Levin, Pistorello, Seeley, and Hayes (2014) within the top 10% of scores on the System Usability Scale (Tullis & Albert, 2008).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…In this section, we review evidence on the efficacy of such treatments and key findings that highlight open questions in their use. EMIs intended to reduce depression do so through interventions aimed at various proximal outcomes such as engagement in pleasurable activities (Ly et al, 2014), increasing positive emotions (Tugade & du Pont, 2014), or other pathways. EMIs for depression have also made use of diverse conceptual treatment strategies including acceptance and commitment therapy (Ahtinen et al, 2013;Lappalainen et al, 2013;Ly, Dahl, Carlbring, & Andersson, 2012) and interpersonal therapy (Dagoo et al, 2014), but the majority have been cognitive-behavioral in focus including cognitive-behavioral therapy (CBT), behavioral activation (Burns et al, 2011), relaxation (Grassi, Preziosa, Villani, & Riva, 2007), and self-monitoring (Agyapong, Ahern, McLoughlin, & Farren, 2012).…”
Section: Emis For Depressionmentioning
confidence: 99%
“…The overall mean age of participants was 45 years (mean age range: 36 -57.6 years). Three studies comprised active comparison groups, including the same MBI delivered in person [41], a web-based behavioural activation condition [44], and a progressive muscle relaxation program [48]. Control conditions were attention control (n=1) [42], online discussion forum (n=2) [43,49], psychoeducational (n=1) [47], wait-list (n=2) [41,45] or usual care (n=2) [36,46].…”
Section: Resultsmentioning
confidence: 99%
“…a primary outcome was feasibility, but sample size was calculated with adequate power to reducing mood disturbance (secondary outcome) OCD = Obsessive compulsive disorder; QE = Quasi-Experimental, QoL = Quality of Life; FU = follow up Studies were published from 2008 and conducted in Sweden (n=3); [43,44,49], Canada (n=2); [41,45], the United States (n=2) [42,46], the Netherlands (n=1); [36], Ireland (n=1); [47] and Germany (n=1); [48]. Eight studies were RCTs [36,[42][43][44][45][47][48][49], and two were quasi experimental design [41,46]. Most studies involved female participants with an overall mean of 74.8%, ranging between 46.3% [36] and 98% [42].…”
Section: Resultsmentioning
confidence: 99%